Threshold changes of ABR results in toddlers and children. (June 2016) - Louza, Julia; Polterauer, Daniel; Wittlinger, Natalie; Muzaini, Hanan Al; Scheckinger, Siiri; Hempel, Martin; Schuster, Maria
Abstract: Introduction: Auditory brainstem response (ABR) is a clinically established method to identify the hearing threshold in young children and is regularly performed after hearing screening has failed. Some studies have shown that, after the first diagnosis of hearing impairment in ABR, further development takes place in a spectrum between progression of hearing loss and, surprisingly, hearing improvement. Objective: The aim of this study is to evaluate changes over time of auditory thresholds measured by ABR among young children. Material and Methods: For this retrospective study, 459 auditory brainstem measurements were performed and analyzed between 2010 and 2014. Hearing loss was detected and assessed according to national guidelines. 104 right ears and 101 left ears of 116 children aged between 0 and 3 years with multiple ABR measurements were included. The auditory threshold was identified using click and/or NB-chirp-stimuli in natural sleep or in general anesthesia. The frequency of differences of at least more than 10 dB between the measurements was identified. Results: In 37 (35%) measurements of right ears and 38 (38%) of left ears there was an improvement of the auditory threshold of more than 10 dB; in 27 of those measurements more than 20 dB improvement was found. Deterioration was seen in 12% of the right ears and 10% of the left ears. Only half of the children had stable hearing thresholds in repeated measurements. The time between the measurements was on average 5 months (0 to 31 months). Conclusion: Hearing threshold changes are often seen in repeated ABR measurements. Therefore multiple measurements are necessary when ABR yields abnormal. Hearing threshold changes should be taken into account for hearing aid provision.